Effects of systemic risk, exchange rate risk and collateral demand: the enforcement of initial margin on South African over‐the‐counter derivatives - Kennedy-Palmer, Storme (School of Economics, 2022)
In their commitment to implementing G20 regulatory reforms to the over‐the‐counter derivatives market, a critical decision faced by South African Authorities is whether to authorise the use of risk‐sensitive models or the standardised schedule to estimate initial margin requirements on non‐centrally cleared derivatives and which central clearing counterparty/ies, if any, to licence. Overburdensome collateral demand has systemic risk implications; therefore, collateral demand for local dealers under three potential market structures is estimated in this study. Initial margin requirements calculated using risk‐ sensitive models vary with market risk to cover counterparty credit risk; thus, the volatility dynamics of the underlying asset are analysed to determine the degree of fluctuation in collateral demand under various market stress scenarios. Lastly, the potential foreign exchange rate exposure to local dealers from licencing an international central clearing party is quantified and examined. Collateral demand calculated with the risk‐sensitive models used by central clearing counterparties and for non‐centrally cleared derivatives is sensitive to the market volatility scenarios, spiking during periods of market stress, highlighting the pro‐cyclical nature of these requirements. The standardised schedule is not pro‐cyclical; however, collateral requirements were found to be higher during tranquil and normal market conditions. Authorities should weigh this trade‐off between microprudential and macroprudential goals. There is an incentive for dealers using the standardised schedule to centrally clear contracts to lower collateral requirements. The sensitivity of collateral demands to other risk‐sensitive model inputs was investigated. It was found that dealers can limit their collateral exposure on non‐centrally cleared derivatives when using the risk‐sensitive approach by using a higher decay factor and VaR risk measure if Authorities do not prescribe these. The most significant reduction of initial margin on both centrally and non‐centrally cleared derivatives can be achieved by dealers balancing their books instead of relying on more complicated delta hedging techniques. Should an international clearing counterparty be licenced, Authorities should be prepared for a substantial increase in the demand for foreign currency. The transaction foreign exchange rate exposure was measured in USD and GBP, and it was found that the exposure demanded in USD was lower and relatively more stable than that in GBP. Authorities could significantly reduce foreign exchange rate exposure by licensing domestic central clearing counterparty/ies instead of international clearers.